Influence of FOMO, Information, and Influencers on Crypto Investment Decisions - Sinaga, Alexander Jerico Nehemia; Usman, Osly (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
This research examines the influence of social media influencers and information accessibility on cryptocurrency investment decisions among Generation Z, with Fear of Missing Out (FOMO) as a mediating variable. A sample of 156 students from Universitas Negeri Jakarta participated in an online survey, and data was analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) to assess both direct and indirect effects. Findings reveal that social media influencers significantly and positively impact investment decisions and FOMO, while ease of information access notably affects both FOMO and investment decisions. Moreover, FOMO mediates the relationship between influencers, information access, and investment decisions. These results highlight the psychological and informational factors influencing Generation Z's cryptocurrency investment behavior, offering insights for stakeholders in financial and digital marketing sectors.